PENGARUH KUALITAS INFORMASI DI INSTAGRAM TERHADAP NIAT BELI PRODUK JANJI JIWA DENGAN VARIABEL KEPERCAYAAN SEBAGAI MEDIASI (STUDI PADA GEN Z DI BANDAR LAMPUNG) - Aqilah Yunda Putria Sari; Satria Bangsawan; Nuzul Inas Nabila (Nusantara Hasana Journal, 2025)
This study aims to examine the influence of information quality delivered through Instagram on purchase intention of Janji Jiwa products, with trust as a mediating variable among Generation Z in Bandar Lampung. Social media, particularly Instagram, serves as a crucial tool in digital marketing strategies, especially in shaping consumer perceptions and purchasing decisions. This research employs a quantitative approach with a survey method involving 143 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that information quality has a significant positive effect on trust, and trust positively affects purchase intention. Furthermore, information quality also directly affects purchase intention while simultaneously influencing it indirectly through trust. This indicates that trust partially mediates the relationship between information quality and purchase intention, where information quality still exerts a direct effect even as trust strengthens the relationship. These findings highligh the importance of delivering relevant and up-to-date information in building trust and encouraging purchase intention among Generation Z consumers.